Multidimensionality of centripetal and centrifugal nationalisms - Romão, Filipe Vasconcelos (2014)
Traditionally, authors focus on the speech of political actors and how these define themselves in order to identify the presence of nationalist political trends. This paper aims to present a wider analytical grid so as to include how nationalism is manifested. In line with this multidimensional proposal, we aim to identify differences as to how nationalisms are made manifest according to their relation with power.